Estudio preliminar acerca de la geología, petrografía y geoquímica del volcán Sara Sara (Ayacucho) en el sur del Perú - Cueva Sandoval, Kevin Arnold (2018)
The Sara Sara volcano (5505 masl.) is a composite volcano located south of the department of Ayacucho in Perú. This volcano is characterized by a series of eruptions of magnitude between 3 and 5. According to the stratigraphy and location of the Sara Sara erupted deposits, (1) the first eruptive episode termed "Sara Sara I" was effusive with lava flows, (2) the period "Sara Sara II" was dominated by an explosive activity resulting in pumice and ash-rich pyroclastic-flow deposits, followed by (3) growth and collapse of summit domes. Later, the period "Sara Sara III" was dominated by fallout deposits, products of Plinian and sub-Plinian eruptions. (4) The most recent effusive eruptive period termed "Sara Sara IV" produced relatively youthful lava flows. The rocks show a mineralogical ensemble of plagioclase, quartz, biotite, amphibole, oxides and volcanic glass. The composition of lavas ranges from dacites (65.1-69.9 wt.% SiO2) to rhyolites (70.1-73.6 wt.% SiO2). Los diagramas de elementos traza no presentan cambios significativos entre las diferentes etapas evolutivas del volcán Sara Sara.